Areal-source and fault-source based probabilistic seismic hazard analysis using characteristic earthquake model and Monte-Carlo approach: An example of the Gulf of Aqaba region - Vladimir Sokolov; Hani Mahmoud Zahran; Mostafa Toni (Soil Dynamics and Earthquake Engineering, 2024)

Nubian aquifer linkage to the High Aswan Dam Reservoir: Initial assessments of processes and challenges - Mohamed Ramah; Essam Heggy; Ahmed Nasr; Mostafa Toni; Mohamed M. Gomaa; Emmanuel Hanert; Adel Kotb (Journal of Hydrology, 2024)

Depicting the main structural affected trends by operating aeromagnetic survey in the western part of Koraimat-Alzafarana road and surround area, Eastern Desert, Egypt - Alaa M. Eweis; Mostafa Toni; Alhussein Adham Basheer (Modeling Earth Systems and Environment, 2022)

Crustal thickness and structural pattern evaluation of Sinai Peninsula using three-dimensional density modeling with aeromagnetic and earthquake data - Gaber M. Gaber; Salah Saleh; Mostafa Toni (Acta Geophysica, 2022)
The Sinai Peninsula is a subplate located between the African and Arabian plates. It is an important subplate in the world; however, this region is poorly understood because of the shortage of geophysical data. Thus, this study focuses on built a three-dimensional (3D) high-resolution forward model of the crustal thickness with a new tectonic model and structural evaluation of the Sinai Peninsula to understand this area tectonically and determine its lithospheric and crustal thicknesses. Qualitative and quantitative interpretations of Bouguer gravity, reduced-to-the-pole (RTP) aeromagnetic, and earthquake data are explained to achieve the goals of this study. Two-dimensional (2D) interactive sequential modeling of gravity data is performed along with some well-selected profiles with existing crustal layer depth points from previous works in the studied region. Seventeen 2D models are constructed and used to determine the basement, Conrad (lower crust boundary), and Moho (upper mantle boundary) depths and to build a 3D model. Accuracy of the 3D built model is evaluated by extracting observed, calculated, and residual gravity anomaly maps. The results show that the basement rocks appear on the surface in the South of Sinai and deepen (down to 4.5 km) toward the North. The Conrad surface varies approximately from 16 km (in the northeast and southwest of Sinai) to 22.8 km (in the southeast). The Moho surface depth (i.e., crustal thickness) varies approximately from 28.8 to 34.2 km, and it deepens toward the northeastern and southwestern parts of Sinai. A tentative basement structure map is constructed from the horizontal gradient (H-gradient) filter and the 3D Euler deconvolution of the Bouguer gravity and RTP aeromagnetic data. Correlation between the geological background of the study area and the obtained results suggests that the Sinai Peninsula is tectonically active, mainly in its southern portion due to the tectonic movements along the Gulf of Suez and the Gulf of Aqaba. The crustal thickness increases southward and thins northward.

Magnitude of completeness for the Northern stations of the Egyptian National Seismological Network - H. E. Abdel Hafiez; Mostafa Toni (Arabian Journal of Geosciences, 2020)

Active tectonic structures in northeastern Egypt: a geospatial analysis using structural, remote sensing, and seismic data - Wael Hagag; Safaa Hassan; Mostafa Toni (Arabian Journal of Geosciences, 2019)

Ambient Noise Level and Site Characterization in Northern Egypt - H. E. Abdel Hafiez; Mostafa Toni (Pure and Applied Geophysics, 2019)

Source mechanism and parameters of the 19 October 2012 earthquake, northern Egyptian continental margin - Awad Hassoup; Mostafa Toni; M. M. F. Shokry; A. M. A. Helal; Emad K. Mohamed (Arabian Journal of Geosciences, 2016)